Analysis of CCDC6 as a novel biomarker for the clinical use of PARP1 inhibitors in malignant pleural mesothelioma. (September 2019) - Morra, Francesco; Merolla, Francesco; D'Abbiero, Debora; Ilardi, Gennaro; Campione, Severo; Monaco, Roberto; Guggino, Gianluca; Ambrosio, Francesca; Staibano, Stefania; Cerrato, Aniello; Visconti, Roberta; Celetti, Angela
Highlights: CCDC6 and BAP1 biochemically interact and act in the DSBs HR-DNA repair in MPM. Loss of CCDC6 induces PARP inhibitors sensitivity in MPM cells. BAP1 defects enhance the response to PARP inhibitors in CCDC6 defective cells. Defects of CCDC6 and BAP1 correlate in 30% of MPM patients. Combined immunostaining of CCDC6 and BAP1 may select MPM patients for DDR targeting. Abstract: Objectives: CCDC6 (coiled-coil domain containing 6) is a player of the HR response to DNA damage and has been predicted to interact with BAP1, another HR-DNA repair gene highly mutated in Malignant Pleural Mesothelioma (MPM), an aggressive cancer with poor prognosis. CCDC6 levels are modulated by the deubiquitinase USP7, and CCDC6 defects have been reported in several tumors determining PARP-inhibitors sensitivity. Our aim was to investigate the functional role of CCDC6 in MPM carcinogenesis and response to PARP-inhibitors. Materials and Methods: The interaction between CCDC6 and BAP1 was confirmed in MPM cells, by co-immunoprecipitation. Upon USP7 inhibition, that induces CCDC6 degradation, the ability to repair the DSBs and the sensitivity to PARP inhibitors, was explored by HR reporter and by cells viability assays, respectively. A TMA including 34 MPM cores was immunostained for CCDC6, USP7 and BAP1 and the results correlated by statistical analysis. Results: MPM cells depleted of CCDC6 showed defects in DSBs repair and sensitivity to PARP inhibitors. The silencing of CCDC6 when combined with the overexpression of BAP1-mutant (Δ221-238) enhanced the HR-DNA repair defects and the PARP inhibitors sensitivity. In the TMA of MPM primary samples, the staining of CCDC6 and of its de-ubiquitinase USP7 showed a significant correlation in the tested primary samples (p = 0.01). CCDC6 was barely detected in 30% of the tumors that also carried BAP1 defects. Conclusion: The combination of CCDC6 and BAP1 staining may indicate therapeutic options for DDR targeting, acting in synergism with cisplatinum.